2012
DOI: 10.1016/j.jjcc.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of forest bathing on human hypertension in the elderly

Abstract: Our results provided direct evidence that forest bathing has therapeutic effects on human hypertension and induces inhibition of the renin-angiotensin system and inflammation, and thus inspiring its preventive efficacy against cardiovascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(262 citation statements)
references
References 35 publications
8
238
1
15
Order By: Relevance
“…Consistent with previous studies [3,22,24,25,40], our study results showed a decrease in middle-aged women' SBP and DBP after the forest therapy program. Though the decline of DBP was not statistically significant in this study, our results suggest the positive effects of forest environments on physical health among middle-aged women.…”
Section: Response Of Blood Pressuresupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [3,22,24,25,40], our study results showed a decrease in middle-aged women' SBP and DBP after the forest therapy program. Though the decline of DBP was not statistically significant in this study, our results suggest the positive effects of forest environments on physical health among middle-aged women.…”
Section: Response Of Blood Pressuresupporting
confidence: 93%
“…First, environmental factors such as temperature, humidity, negative air ions, and illumination were not considered in this study. Previous studies have confirmed that many environmental factors are associated with psychological and physiological health [3,14,45]. Therefore, it is suggested that the above-mentioned factors be controlled in future studies in order to give a more precise estimation regarding the effects of visiting a forest.…”
Section: Experimental Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the study design, 11 studies used a crossover trial design and only six of the studies [16,[18][19][20][21][22] used a randomized controlled trial (RCT) design. Four out of six RCT design studies were conducted with adults with health problems.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For articles published in English, nine studies [12,19,21,22,25,28,29,34,39] used POMS to assess the level of depression and three studies [28,29,39] used Semantic differential (SD) method. Other scales used by the studies included the Hamilton Rating Scales for Depression [20], Beck Depression Inventory (BDI) [16,20,24,31], positive and negative affect schedule (PANAS) [34].…”
Section: Depression Measuresmentioning
confidence: 99%